Human performance in air traffic control - Edwards, Tamsyn (2013)
Air Traffic Controllers (ATCOs) are responsible for the safety and efficiency of all air traffic. It is essential that controllers maintain a consistently high standard of human performance in order to maintain flight safety. Knowledge of human factor influences on controller performance is critical to understand and mitigate threats to performance.